Reading the Pentateuch's genealogies after the exile : the Chronicler's usage of Genesis 1-11 in negotiating an All-Israelite identity - Jonker, Louis C. (Old Testament essays, 2012)
From the first nine chapters of Chronicles it becomes clear that not only Samuel-Kings were used as sources by the Chronicler, but also the Pentateuch. The Chronicler was certainly one of the earliest readers of the Pentateuch (in whatever form) after the exile. The peculiarity of the Chronicler's version of Israelite history starting with "Adam" has been noted by many scholars. It seems as if the Chronicler particularly found the genealogies in Gen 1-11 useful to legitimize a universal context for negotiating the identity of All-Israel in the late Persian Period. This contribution will examine some of the Chronicler's genealogies in synoptic comparison with the genealogies of the Urgeschichte in order to determine how and why this exilic literature was used in Chronicles at a later stage in the literary history of the Hebrew Bible, as well as to establish what we can learn about the literary history of the Pentateuch from the Chronicler's usage.